2014
DOI: 10.1039/c4ra10075a
|View full text |Cite
|
Sign up to set email alerts
|

Highly strong and highly tough electrospun polyimide/polyimide composite nanofibers from binary blend of polyamic acids

Abstract: Electrospun blend-polyimide (blend-PI) nanofibers with high tensile strength and toughness are highlighted in this article. The blend-PI nanofibers were prepared by electrospinning the binary blend of rigid and flexible polyamic acids, followed by thermal imidization. The method is simple and can be extended to other kinds of polyamic acids. The morphologies and structures of the blend-PI nanofibers were investigated by scanning electron microscopy (SEM) and wide-angle X-ray diffraction (XRD). The mechanical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Previous work found that the electrospun PI nanofibers possessed excellent mechanical strength [13], superior thermal stability [14], and super high toughness [13], which made them excellent candidates as reinforcements [15,16] and the layer-by-layer hot pressing can improve the uniformity and reduce the porosity of polymer-based composites [17][18][19]. Therefore, in this work, we choose high performance electrospun copolyimide (co-PI) nanofibers as reinforcement and high dielectric performance PVDF as matrix to prepare nanofiber reinforced all-organic composites.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work found that the electrospun PI nanofibers possessed excellent mechanical strength [13], superior thermal stability [14], and super high toughness [13], which made them excellent candidates as reinforcements [15,16] and the layer-by-layer hot pressing can improve the uniformity and reduce the porosity of polymer-based composites [17][18][19]. Therefore, in this work, we choose high performance electrospun copolyimide (co-PI) nanofibers as reinforcement and high dielectric performance PVDF as matrix to prepare nanofiber reinforced all-organic composites.…”
Section: Introductionmentioning
confidence: 99%
“…Both PI membranes exhibited a much higher stress than the neat PAA membrane, $29 kgf cm À2 , due to imidization. 15,[30][31][32] In particular, the hotpress-induced PI membrane ($220 kgf cm À2 ) displayed a notably increased stress compared to the thermally-treated PI membranes ($107 kgf cm À2 ). This higher value for the mechanical property could be explained by the dense packing of the nanober layers and the inter-nanober interactions, as briey mentioned above.…”
Section: Resultsmentioning
confidence: 96%
“…When compared to neat films of rigid PIB with high modulus and flexible PIO with high elongation, the blend PI (at the 7/3 molar ratio of PIB and PIO) not only possessed a higher strength but also a higher elongation. Previous studied have demonstrated that intermolecular interactions play a more important role in the improvement of the mechanical properties . Thus, changes in the intermolecular interactions, such as π–π stacking, crystallinity, and macromolecular orientation, will result in tremendous changes in mechanical properties.…”
Section: Resultsmentioning
confidence: 99%